(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
Abstract In 2010, the Religious Training Center (RTC) of Semarang implemented Distance Education and Training (DET) with the subjects of Mathematics for Islamic Junior High School (MTs) and CheÂmistry for Islamic Senior High School (MA). DET was implemented to provide more education and training for officers of the Ministry of Religious Affairs amidst various limitations of costs, study space, transportation, and teachersâ€™ obligation to conduct qualified and continuous teaching. This study aims to evaluate the implementation of the DET by the RTC of Semarang. The methods and techniques used were interviews, document review, observation, and deployment of questionnaire, which mostly employed the qualitative analysis. The purpose of this study is to determine the context of the DET implementation, inputs, processes, and its products. The findings show that the DET in the RTC of Semarang has generally been carried out as planned, and needs to be continued, even propagated with a number of improvements, in terms of inputs, processes and products. Abstrak Pada tahun 2010, Balai Diklat Keagamaan (BDK) Semarang melaksanakan Diklat Jarak Jauh (DJJ) dengan materi pelajaran Matematika untuk Madrasah Tsanawiyah dan Kimia untuk Madrasah Aliyah. DJJ dilaksanakan untuk dapat lebih banyak mendiklat pegawai Kemenag di tengah berbagai keterbaÂtasan biaya, ruang belajar, transportasi, dan kewajiban guru untuk mengajar secara berkualitas dan kontinyu. Penelitian ini bertujuan untuk melakukan evaluasi pelaksanaan DJJ pada BDK Semarang. Metode dan teknik yang digunakan adalah wawancara, telaah dokumen, pengamatan, dan penyebaran angket yang lebih dengan analisis secara kualitatif. Tujuan penelitian ini adalah untuk mengetahui konteks penyelenggaraan DJJ, input, proses, dan produknya. Hasil penelitian menunjukkan bahwa DJJ pada BDK Semarang secara umum telah terlaksana sesuai yang direncanakan, dan perlu dilanjutkan, bahkan diperbanyak dengan sejumlah perbaikan baik dari segi input, proses maupun produknya.